O capodoperă a literaturii române din secolul al XVIII-lea - Dan Zamfirescu (Revista de Istorie și Teorie Literară)
This study presents and edits ms. I 2033 (State Archive – Piatra Neamţ), containing True Copy for (or, in other copies of the manuscript, History of) the Saint Icon of the Mother of God from Neamţ Monastery by Metropolitan George IV of Moldavia (1723–1729) for the very first time. This text describes the circumstances in which the icon arrived in Neamţ, as the journey made by the future Byzantine emperor John VIII Paleologus through Moldavia and his meeting with Alexander the Good, long thought to be a mere legend, but which is actually based on historical facts.